Acceleration effect of synthesised calcium silicate hydrate with different morphologies and Ca/Si on cement hydration. Issue 9 (6th July 2018) - Zhang, Hao; Wang, Penggang; Li, Wei; She, Wei
Abstract : Synthetic calcium silicate hydrate (C–S–H) is an important accelerator in cement chemistry. The early age hydration of cement was studied in the presence of synthetic C–S–H of different Ca/Si ratios and in different morphologies. Compressive strength, isothermal conduction calorimetry, zeta potential and inductively coupled plasma–optical emission spectroscopy were employed to investigate the acceleration efficiency. Results show that the extent of the acceleration was dependent on the amount, the morphologies and the chemical composition of the C–S–H, but not in a linear way; however, the acceleration efficiency was closely related to the specific surface area. It is suggested that the specific surface area is the main indicating factor for the acceleration efficiency. The induction period of cement hydration was shortened because the rate and the degree of dissolution of cement were increased while the secondary nucleation process energy of C–S–H was decreased. This paper provides an understanding of the effect of synthetic C–S–H of different Ca/Si ratios and morphologies on cement hydration and also sheds new light on the optimising effect of synthetic C–S–H on cement-based materials.